Regional approach to modeling the transport of floating plastic debris in the Adriatic Sea. Issue 1 (15th February 2016) - Liubartseva, S.; Coppini, G.; Lecci, R.; Creti, S.
Abstract: Sea surface concentrations of plastics and their fluxes onto coastlines are simulated over 2009–2015. Calculations incorporate combinations of terrestrial and maritime litter inputs, the Lagrangian model MEDSLIK-II forced by AFS ocean current simulations, and ECMWF wind analyses. With a relatively short particle half-life of 43.7 days, the Adriatic Sea is defined as a highly dissipative basin where the shoreline is, by construction, the main sink of floating debris. Our model results show that the coastline of the Po Delta receives a plastic flux of approximately 70 kg(km day) -1 . The most polluted sea surface area (> 10 g km -2 floating debris) is represented by an elongated band shifted to the Italian coastline and narrowed from northwest to southeast. Evident seasonality is found in the calculated plastic concentration fields and the coastline fluxes. Complex source–receptor relationships among the basin's subregions are quantified in impact matrices. Highlights: Identification of the plastic floating debris inputs into the Adriatic Sea. Markov chain model is constructed based on the Lagrangian model dataset. The model indicates a high dissipativity of the Adriatic due to intensive beaching. Regional source–receptor relationships are quantified by means of impact matrices.